Zalety i wady żyda w pojedynkę w percepcji młodych dorosłych nie posiadających partnera życiowego - Palus, Katarzyna (Wydawnictwo Naukowe UAM, 2010)
The research field of this paper are the advantages and disadvantages of singlehood in young adult singles' perception. This subject, surprisingly, arouses greater interest among sociologists and demographers than among psychologists. The consequences of this state of affairs is that information about the psychological issues of the nevermarried population is limited. The goal of the study was to see the advantages and disadvantages of in young adults' perception. This research so called narrative-biographical interviews proposed by Schiitze was conducted with 36 participants not having partners (22 women and 14 men) in the age of 21-30 years. Participants' responses were grouped into five categories referring to advantages of being singled. I called these categories as follows: (1) "Independence and freedom", (2) "Time for myself", (3) "No emotional sacrifice", (4) "No advantages ", (5) "Fewer expenses". The participants' responses were also grouped into five categories referring to disadvantages of being singled. I called these categories as follows: (1) "The lack of emotional and physical closeness", (2) Lonely , (3) "No disadvantages", (4) "The pressure of environment ", The main conclusion of this study is that in young adults singles' perception it is hard to indicate exclusively there are only advantages and disadvantages of their singlehood. This situation is related both with advantages and disadvantages and we cannot state that singlehood means only bright or dark sides of life.
Advantages and disadvantages of singlehood in young adult singles' perception